2022
DOI: 10.1039/d1ob02414k
|View full text |Cite
|
Sign up to set email alerts
|

Controlled reduction of activated primary and secondary amides into aldehydes with diisobutylaluminum hydride

Abstract: A practical method is disclosed for the reduction of activated primary and secondary amides into aldehydes using diisobutylaluminum hydride (DIBAL-H) in toluene. A wide range of aryl and alkyl N-Boc,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In the last few years, our group has been focused on amide activation reactions. In this context, we have demonstrated tert-butyl nitrite mediated transamidation of secondary amides, [8] transformation of N-Boc-amides into aryl ketones with Grignard reagents, [9] diversification of α-ketoamides via transamidation reactions [10] and controlled reduction of N-Boc and N-Ts amides into aldehydes with DIBAL-H. [11] In transamidation reactions, undoubtedly, Boc-activated amides are more reactive due to high steric distortion. The N-Boc amides are typically prepared from corresponding amides and Boc-anhydride in the presence of a base.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the last few years, our group has been focused on amide activation reactions. In this context, we have demonstrated tert-butyl nitrite mediated transamidation of secondary amides, [8] transformation of N-Boc-amides into aryl ketones with Grignard reagents, [9] diversification of α-ketoamides via transamidation reactions [10] and controlled reduction of N-Boc and N-Ts amides into aldehydes with DIBAL-H. [11] In transamidation reactions, undoubtedly, Boc-activated amides are more reactive due to high steric distortion. The N-Boc amides are typically prepared from corresponding amides and Boc-anhydride in the presence of a base.…”
Section: Introductionmentioning
confidence: 97%
“…In the last few years, our group has been focused on amide activation reactions. In this context, we have demonstrated tert ‐butyl nitrite mediated transamidation of secondary amides, [8] transformation of N ‐Boc‐amides into aryl ketones with Grignard reagents, [9] diversification of α‐ketoamides via transamidation reactions [10] and controlled reduction of N ‐Boc and N ‐Ts amides into aldehydes with DIBAL‐H [11] …”
Section: Introductionmentioning
confidence: 98%
“…[6] Over the past few years, our research group has been focused on the amide activation reactions and reported transamidation of secondary amides via N-nitroso [7] and N-Cbz [8] amide intermediates, syntheses of aryl ketones from N-Boc-amides, [9] and partial reduction of N-Boc and N-Ts amides into aldehydes. [10] Moreover, we have recently reported the transamidation approach for the facile synthesis of N-alkyl and N-benzyl α-ketoamides from N-tosyl and N-Boc αketoamides at room temperature. [11] Very interestingly, N-tosyl α-ketoamides underwent transamidation with alkyl amines in the absence of base or catalyst, while Cs 2 CO 3 was used to promote the transamidation in N-Boc α-ketoamides.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4e,f] Nevertheless, N-aryl α-ketoamides are important scaffolds in synthetic organic chemistry and medicinal chemistry (Figure 1). [1][2][3] Considering these facts and in continuation of our previous works in transamidation, [7][8][9][10] here we explored the synthesis of N-aryl α-ketoamides, α-ketoesters and α-ketothioesters via transamidation reaction in the presence of organic base DBU under metal free conditions (Scheme 1). In addition, we have also explored the regioselective synthesis of biologically relevant quinoxalinones from Naryl α-ketoamides via nitration followed by reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation